2023
DOI: 10.3390/app13042740
|View full text |Cite
|
Sign up to set email alerts
|

Process Optimization of Microwave-Assisted Extraction of Chlorophyll, Carotenoid and Phenolic Compounds from Chlorella vulgaris and Comparison with Conventional and Supercritical Fluid Extraction

Abstract: The production of bioactive products from microalgae biomass with efficient and environmentally friendly technologies is a field of great research interest. The present work focuses on the recovery of high-added value bioactive components from Chlorella vulgaris through microwave-assisted extraction (MAE) with aq. ethanol 90% v/v. The effect of extraction temperature (40–60 °C), duration (5–25 min), solvent-to-biomass ratio (20–90 mLsolv/gbiom), and microwave power (300–800 watts) was investigated regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…On the other hand, the TPC content in leaf extracts obtained by MAE and ASE was almost identical to those obtained after 30 min of CE (10,652.7 mg/100 g), demonstrating the advantages of MAE and ASE, namely the decrease in extraction time and solvent consumption. A similar trend was observed by Ince et al [61] for aerial parts of dry nettle extracts, by Elez Garofulić et al [18] for Pistacia lentiscus L. fruit and leaves extracts, by Georgiopoulou et al [62] for Chlorella vulgaris extracts, and by Alhallaf et al [63] for nonotus obliquus (chaga) sclerotia extracts.…”
Section: Comparison Between Ce Mae and Asesupporting
confidence: 75%
“…On the other hand, the TPC content in leaf extracts obtained by MAE and ASE was almost identical to those obtained after 30 min of CE (10,652.7 mg/100 g), demonstrating the advantages of MAE and ASE, namely the decrease in extraction time and solvent consumption. A similar trend was observed by Ince et al [61] for aerial parts of dry nettle extracts, by Elez Garofulić et al [18] for Pistacia lentiscus L. fruit and leaves extracts, by Georgiopoulou et al [62] for Chlorella vulgaris extracts, and by Alhallaf et al [63] for nonotus obliquus (chaga) sclerotia extracts.…”
Section: Comparison Between Ce Mae and Asesupporting
confidence: 75%
“…The effects of the SFE (10% (w/w) of ethanol, 250 bars, 60 • C, flow rate of 40 g/min, and total solvent consumption of 100 kg CO 2 / kg biomass) on the extraction of carotenoids from C. vulgaris were also evaluated. According to this study, the use of this method resulted in approximately 1.8-and 1.4-fold increases in the total amounts of extracted carotenoids when compared to that of a conventional solid-liquid extraction (aqueous ethanol 90% (v/v), 24 h) and a MAE method (60 • C, 300 W, 14 min, and 22 mL/g (solvent/biomass)), respectively [38]. The SFE of carotenoids has been also optimized in several matrices, such as pink grapefruit (325 bar, 64 • C, and 143 min, rice bran oil as co-solvent, CO 2 and rice bran oil flow rate set at 35 g/min, and 3% of CO 2 (w/w)) or carrot peel (349 bar, 80 min, 59 • C, 15.5% ethanol as co-solvent, CO 2 flow rate of 15 g/min) [39,40].…”
Section: Supercritical Fluid Extractionmentioning
confidence: 82%
“…The same group has also used a Face-Centered Central Composite Design (FC-CCD) with RSM to optimize the process of MAE to obtain chlorophyll, carotenoid, and phenolic compounds from a microalga, Chlorella vulgaris, and compared the results with those obtained from SLE and SFE [27]. They have found that, under the optimized conditions, the percentage extraction yield obtained by SLE was higher than that obtained by MAE, which was, in turn, higher than that obtained by SFE.…”
Section: Discussionmentioning
confidence: 99%